(untitled) (Archaeologia Adriatica, 2009)
During field surveys of the Lower Herzegovina region to establish the condition of cultural monuments, the staff of the Department for Protection of Cultural and Historical Heritage of Herzegovina-Neretva Canton noted and registered in 2003 and 2004 a large number of previously unknown or merely sporadically mentioned sites at which the existence of Early Christian walled grave vaults can be established or conjectured. Their common feature is a stone construction with a barrel vault of stone or travertine, with one or two flat stone bases in the grave chamber, although a vault type without such stones also appears. Walled grave vaults as a rule were tied to Early Christian sacral architecture, while the impossibility of connecting individual grave vaults discovered by chance to religious structures is caused by the lack of systematic archaeological research. So far around 80 grave vaults have been registered in Bosnia and Herzegovina, which were probably family grave vaults of the upper class, perhaps of owners of the estates on which churches were built. On the basis of the architecture of individual graves beneath stećci (monumental tombstones) in the area under consideration, related to the manner of constructing grave vaults, a continuity of burial can be conjectured at Early Christian sites all the way to the late medieval period.